2020
DOI: 10.1371/journal.pone.0242418
|View full text |Cite
|
Sign up to set email alerts
|

Providing person-centered care for patients with complex healthcare needs: A qualitative study

Abstract: Background People with chronic conditions have complex healthcare needs that lead to challenges for adequate healthcare provision. Current healthcare services do not always respond adequately to their needs. A modular perspective, in particular providing visualization of the modular service architecture, is promising for improving the responsiveness of healthcare services to the complex healthcare needs of people with chronic conditions. The modular service architecture provides a comprehensive representation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 45 publications
1
24
0
Order By: Relevance
“…Therefore, our sample of six healthcare professionals might not be representative of the experiences and concerns of parents and healthcare professionals caring for individuals with Down syndrome in other parts of the world. Nevertheless, previous research has shown that the organisation of care for individuals with Down syndrome is fairly similar throughout the Netherlands (Peters et al, 2020). In addition, parents were considered as proxies for children with Down syndrome in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Therefore, our sample of six healthcare professionals might not be representative of the experiences and concerns of parents and healthcare professionals caring for individuals with Down syndrome in other parts of the world. Nevertheless, previous research has shown that the organisation of care for individuals with Down syndrome is fairly similar throughout the Netherlands (Peters et al, 2020). In addition, parents were considered as proxies for children with Down syndrome in our study.…”
Section: Discussionmentioning
confidence: 99%
“…This professional would have an up-to-date overview of the complexity of different health problems of the child with Down syndrome, an overview of the different healthcare providers involved, and help to find the healthcare needed. Literature shows that the presence of a coordinator who coordinates the entire process increases the chance of the transition's success (Bindels-de Heus et al, 2013;Dimitropoulos et al, 2019;Goralski et al, 2017;van den Driessen Mareeuw et al, 2020;Viner, 1999;White & Cooley, 2018) fairly similar throughout the Netherlands (Peters et al, 2020). In addition, parents were considered as proxies for children with Down syndrome in our study.…”
Section: Continuity Of Care Was Highlighted By Professionals and Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the growing body of research on service modularity, practical applications of modular delivery are relatively rare (de Mattos et al, 2019) in other service contexts except reported cases in healthcare (Peters et al, 2020), logistics (Cabigiosu et al, 2015), IT (Tuunanen et al, 2022), education (Sorkun et al, 2022), legal services (Giannakis et al, 2018), and tourism (Avlonitis & Hsuan, 2017). The literature offers little in the way of decision support for planning modular service delivery and weighing the changes to be implemented.…”
Section: Introductionmentioning
confidence: 99%